LEGEA TRUPULUI – POVESTEA UNEI VIEȚI. O CARTE DE DEBUT JUCATĂ PREA TÂRZIU (Analele Universității București. Limba și literatură română, 2025)
The Body’s Rule – The Tale of a Life, the first novel written by Agârbiceanu (in 1911), only appeared in book form in 1926. The novel – which held significant potential for the chronology of the Romanian novel at the time of its serialized publication (1912) – was initially "forgotten", due to the political instability preceding World War I, and further delayed by the Great Union of 1918 and its author's subsequent turn toward politics and journalism. By the time of its book publication in 1926, the literary landscape had changed so dramatically that the novel quickly became obsolete. However, when restored to its historical place, it reveals itself as a relevant work for the early stages of Realism and a worthy representative of the 20th century Central European fiction.
Keywords: Agârbiceanu; Legea trupului; debut novel; realism; Central European fiction